An anthropology of the subject : holographic worldview in New Guinea and its meaning and significance for the world of anthropology - Wagner, Roy, 1938-2018 (University of California Press, 2001)
An Anthropology of the Subject rounds out the theoretical-philosophical cosmos of one of the twentieth century's most intellectually adventurous anthropologists. Roy Wagner, having turned "culture" and "symbols" inside out (in The Invention of Culture and Symbols That Stand for Themselves, respectively), now does the same for the "subject" and subjectivity.